COVID-19 Outbreak Impact on Stock Return in Indonesia and Malaysia - Merinda Wijaya; Hesniati Hesnaiti; Robin Robin; Ferdinand Nainggolan (University of Merdeka Malang, 2022)
The COVID-19 outbreak drastically impacts the worldwide economy including the stock returns. This study uses Indonesia and Malaysia cases with a total of 141.585 and 219.381 observations in 2020. The measurement of COVID-19 of this study uses daily new confirmed cases and daily death cases from each country. To test the hypothesis, an unbalanced panel and multiple regression are used to test the crowded data. The results show different results for each country. In Indonesia, we found that the COVID-19 outbreak is a strong negative effect on stock return, in contrast, Malaysia found it to be less influence. Furthermore, the effect of Monday and Friday was used to test any impact of the day during the pandemic on stock return. Surprisingly, the effect of Friday affects different from Monday. The weekend effect still occurs in a pandemic situation and the investor mood sentiment to Indonesia’s stock market. This could be one of the aspects for investors consider when making investment decisions during a pandemic.